Strategies to Develop Healthier Meat and Meat Products - Biswas, A. K.; Mandal, P.K.; Jairath, Gauri (Journal of Meat Science, 2016)
The extensive use of chemical preservatives in food processing industry and their association with health related problems has increased the demand for development of products which are safe, natural and contain fewer food additives. The current strategies in development of healthier meat and meat products are through genetic improvement, nutritional manipulation, feeding management practices, reformulation of meat products including use of natural antioxidants and antimicrobials from plant extracts and their essential oils, enzymes, peptides, bacteriocins, bacteriophages and fermented ingredients. These strategies actually lead to development of healthier meat and meat products with the concurrent improvement of functional compounds. Antioxidant and /antimicrobial activities of some spices, herbs and other plant extracts and/or their essential oils are mainly due to the presence of some bioactive compounds like phenolics, flavonoids, aldehydes and terpenes. Reduction of some specific unhealthy compounds like cholesterol, fat, sodium, nitrites and even lowering of calorie content are other strategies to develop healthier meat and meat products. Functional compounds, especially antihypertentive peptides, opioid peptides, antioxidative peptides can also be generated from meat and meat products during processing such as fermentation, curing and aging. The use of these ingredients in meat products offers processors the opportunity to improve the nutritional and health benifits of their products. An overview of the research works done on the development of healthier meat and meat products adopting different strategies is presented in this review.
Keywords: Designer meat; Functional meat products; Natural antioxidants; Bio-active compounds; Health foods